Reliability of anthropometric measurements of a digi‐board in comparison to an analog height board in Namibian children under 5 years - Johanna Namene; Christian J. Hunter; Shirley Hodgson; Humphrey Hodgson; Jane Misihairabgwi; Shan Huang; Joel Conkle (Maternal and Child Nutrition)
Abstract Poor measurement quality has set back the utility of anthropometry in defining childhood malnutrition, prompting calls for alternative measurement techniques. This study aimed to assess the reliability of anthropometric measurements using a digital height board in comparison to an analog height board in Namibian children under 5 years of age. A cross‐sectional, descriptive study was conducted (n = 425) between the age of 6 and 59 months, using anthropometric measurements of weight, height and mid‐upper arm circumference. Two trained enumerators each collected four height measurements of each child: two using an analog height board and two using a digi‐board. The repeated height measurements between and within the enumerators were used to determine intra‐ and interobserver reliability. Reliability of the digi‐board was assessed using the technical error of measurement (TEM), relative TEM (%TEM), intraclass correlation and a Bland–Altman analysis to assess the agreement between the two methods. In all these assessments, the analog height board was considered as the gold standard and used for comparison. The digi‐board showed superiority to the analog height board in terms of reliability (analog TEM = 0.22, digi‐board TEM = 0.16). Although the digi‐board has potential to improve child anthropometry, further clinical and large survey studies are needed to validate the used of this tool in routine population‐based surveys.